An Improved Data Set for Antarctica: a Filled and Edited 90m-TanDEM-X Digital Elevation Model - Wessel, Birgit; Huber, Martin; Abdullahi, Sahra; Reuß, Felix; Georg, Isabel; Roth, Achim (2019)
In this study we present the digital elevation model (DEM) for Antarctica produced by the TanDEM-X (TerraSAR add-on for digital elevation measurement) mission. It is composed of more than 41,000 interferometric synthetic aperture radar (InSAR) DEM scenes. The DEM presented here is a reduced version of the TanDEM-X global DEM in a 90m universal polar stereographic (UPS) projection. For Antarctica, special adaptations on the nominal TanDEM-X DEM generation were conducted in particular regarding the DEM calibration. Further improvements on the TanDEM-X DEM version 1.0 were conducted, as holes were filled with new acquisitions leading to a significantly reduced amount of invalid areas. Comparisons with ICESat and Icebridge data are performed. As X- Band SAR penetrates the snow and ice pack by several meters a new concept for absolute vertical ground control points was set up that relies on areas with stable penetration conditions and on ICESat (Ice, Cloud, and land Elevation Satellite) elevations. The resulting DEM is outstanding due to its resolution, accuracy and coverage completeness, especially for Antarctica. The 3-arcsecond version (so-called 90m DEM) is freely available. It provides a high resolution dataset as basis for research, e.g. on climate change, in Antarctica.